PENGARUH TINGKAT PENDIDIKAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN OUTSOURCING PT TELKOM WITEL SOLO - Vira Auzira Rasidi; Anton Subarno; Tutik Susilowati (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
AbstractThe purpose of this research is to determine whether there is or not: 1) the effect of education level on the performance of employees of Outsourcing PT. Telkom Witel Solo. 2) the influence of work discipline on the performance of employees of Outsourcing PT. Telkom Witel Solo. The type of research used is quantitative research with the method of causality description. The population in this study were all outsourcing employees of PT. Telkom Witel Solo, amounting to 59 people. The data collection technique in this study used a census sampling technique with a questionnaire. Hypothesis testing in this study was conducted using logistic regression and simple linear regression. The results showed that: 1) There is no influence between the education level variables on employee performance, this is indicated by the Wald significance, it is known that it is 0.163> 0.05 p-value which is smaller than alpha indicating that Ho is accepted. 2) There is an influence between work discipline variables on employee performance. This is indicated by the t-test value of 4.111, to determine whether or not there is an influence, then the t-count must be greater than the ttable. In this study, the t table with a significant level of 5% and df = 59 (df = n - k - 1, where df = 59 - 2 - 1 = 56), obtained t table of 2.003 or 4.111> 2.003 with a significance value of 0.000 <0.05.Keywords: education level, work discipline, employee performance